1999
DOI: 10.1677/joe.0.1630181
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of beta-cell function and survival following islet isolation requires re-establishment of the islet-matrix relationship

Abstract: Islet transplantation is associated with a high rate of early graft failure, a problem that remains poorly understood. It is probable that the destruction of the islet microenvironment and loss of tropic support that occur during isolation lead to compromised survival. The purpose of this study was to determine the role of matrix-integrin interactions on beta-cell survival and function following islet isolation. Canine islets were obtained by conventional methods. Immediately after isolation, the peri-insular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
298
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(304 citation statements)
references
References 37 publications
5
298
1
Order By: Relevance
“…After 7 days of culture, both the cellular composition and the glucose-induced insulin production per islet had not decreased. In contrast, other studies using cultured islets show a gradual decline in insulin content [25,26], and the glucagon-producing cells have often disappeared. It has been shown that peripheral glucagon secreting cells (alpha cells) are lost during most of the isolation procedures.…”
Section: Discussionmentioning
confidence: 79%
“…After 7 days of culture, both the cellular composition and the glucose-induced insulin production per islet had not decreased. In contrast, other studies using cultured islets show a gradual decline in insulin content [25,26], and the glucagon-producing cells have often disappeared. It has been shown that peripheral glucagon secreting cells (alpha cells) are lost during most of the isolation procedures.…”
Section: Discussionmentioning
confidence: 79%
“…Disruption of inter-islet cell contacts and purification of beta cells away from other cell types possibly contributing to the deposition of ECM components in islet cultures was considered to be a confounding factor in allowing the purified cells to thrive in culture. Until now, there has been no clear information regarding integrin expression on human islet cells aside from indirect data obtained from immunocytochemistry on isolated islets [17,34] or the developing human pancreas [34]. In both instances, limiting resolution and sensitivity of immunocytochemistry made it difficult to ascertain which integrins were truly expressed by beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collagenase digestion of the pancreas to isolate islets [11], and their subsequent dispersion into a single cell preparation [10] involves disruption of cell-cell and cell-extracellular matrix contacts. Such disengagement of cell adhesion molecules and of integrin receptors for elements of the matrix is known to result in perturbation of differentiated function of rodent beta cells [12] and to prejudice cell survival [13], notably by inducing apoptosis and necrosis [14,15,16], as well as a loss of function [17]. Reestablishment of appropriate cell to matrix contacts reduces apoptotic signals [18].…”
mentioning
confidence: 99%
“…This precisely controlled milieu is disturbed by islet processing, which results in the loss of many important physical, cellular and trophic signals required for beta cell differentiation, survival and function [11,12]. Notably, detachment from the ECM has been shown to leave islets prone to fragmentation [5] and susceptible to an increased frequency of apoptotic events [13,14].…”
Section: Introductionmentioning
confidence: 99%